2016
DOI: 10.17656/jzs.10555
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C seropositivity and RNA detection among Type2 Diabetic patients in Sulaimani Governorate-Iraqi Kurdistan Region

Abstract: The current study included 421 cases (221 with type 2 diabetic) and (200 non-diabetics- control group). ELISA and conventional PCR techniques were used for detection of anti-HCV antibodies and HCV-RNA respectively. The percentage rates of HCV seropositivity were (9.5%) among type 2 diabetic patients that were significantly higher (p < 0.05) compared to controls. Moreover, HCV-RNA detection was more frequent among diabetic patients (5.88%), although no significant differences found with non-diabetic cases (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…Although there are no data about HDV infections in our hospitals and community, this is the first study on HDV in Kurdistan. Similar studies done among type II diabetic patients in Sulaimani city reported a lower prevalence of HCV infections [43].…”
Section: Discussionsupporting
confidence: 66%
“…Although there are no data about HDV infections in our hospitals and community, this is the first study on HDV in Kurdistan. Similar studies done among type II diabetic patients in Sulaimani city reported a lower prevalence of HCV infections [43].…”
Section: Discussionsupporting
confidence: 66%
“…These observations were agreed with observation reported by others [14]. In another study done in Sulaimani, it was found that occupation, education level, history of jaundice, smoking, and alcohol drink had a significant effect on viral hepatitis infections, especially HCV infection [15]. Our observations were parallel with their conclusion considering some factors, including smoking.…”
Section: Discussionsupporting
confidence: 93%